Frequency of Abnormal Sperm Motility in Male Smokers with Primary Infertility - Syeda Sahar Zahra, Uzma Khalid, Pari Iman Gul, Asim Iqbal Qureshi, Nimrah Sattar, Ishfaq Ul Haq (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the frequency of abnormal sperm motility and related factors in male smokers with primary infertility. Place and duration of the study: From 8th Feb 2021 to 8th Feb 2022 at Gynaecology Department of Bakhtawar Amin Trust Teaching Hospital Multan for 1 year Study design: A retrospective study Methodology: A total of 120 patients were included in the study among which 100 patients were smokers and 20 patients were non-smokers. For sample collection, patients were asked to masturbate and collect the first portion of ejaculate to ensure the maximum amount of sperm. Semen analysis was done on regular basis under a light microscope according to WHO guidelines. After the semen liquefaction, the 10μl of the sample was analyzed on a glass slide covered with a coverslip. For evaluating the motility, 200 spermatozoa were counted in 5 fields at 200x magnification. Results: Six non-smokers (30%) showed low motility. In comparison, 76 smokers (63.3%) showed low motility. Low motility was observed more in smokers as compared to smokers. The difference between motility in smokers and non-smokers was statistically significant (<0.001) (Chi sq= 23.55). Cigarette smoking also affected the sperm count as 24 (20%) smokers had a low sperm count. Conclusion: Smoking affects vital sperm characteristics such as sperm count and motility and in turn, be a potential cause of subfertility or infertility. Keywords: Cigarette smoking, male fertility, sperm count, sperm motility.